Invest in Education Early, Smartly and for All : Synthesis Report - World Bank (World Bank, Washington, DC, 2020)
The demographic shift occurring in Serbia has had a profound effect on the education system. The student population has declined by 21 percent in primary schools and 13 percent in secondary schools since 2000, but the school network has changed little since then. This has resulted in many schools with few students. Furthermore, the total number of teachers working in the education system has been increasing until very recently, creating further pressures on the education sector wage bill. In recognition of such challenges in the education sector as well as other social sectors, the Government of Serbia has embarked on a program to review the organizational and functional structures of service delivery, supported by a Stand-By Arrangement (SBA) approved by the International Monetary Fund (IMF) in February 2015. The purpose of the program is to enhance productivity and performance in the delivery of public services while also reducing the wage bill in the public administration.